Design of walkway rig system for gait motion tracking of children with cerebral palsy - Mahamud F.; Anuar A.; Aini M.A.M. (Penerbit UTM Press, 2023)
This paper reports the design of walkway rig system for gait motion tracking of children with cerebral palsy (CP) at Universiti Tenaga Nasional (UNITEN), Malaysia. The walkway rig consists of a modular walkway platform, adjustable parallel bar, and overhead gantry with body support harness system. The rig has been designed to support different modes of walking assistance depending on a subjects walking capability. The modes of walking assistance are body weight support system, parallel bars along walkway, usage of walker, and human assisted. The key feature of this system lies in the flexibility of it to enable more options during gait motion tracking for CP children. System design and stress analysis were done using CAD software. The design is evaluated using virtual mannequins to check the functions and suitability for CP children. The evaluation shows that the proposed system is feasible to be implemented for CP children gait motion tracking. 2015, Penerbit UTM Press. All rights reserved.